Scoring Procedures for Assessing Writing - Taejoon Park (Studies in Applied Linguistics & TESOL, 2003)
The evaluation of writing ability of L2 students has become increasingly important in recent years, because the results of such evaluations are used for a variety of administrative, instructional, and research purposes. One of the first decisions to be made in determining a system for directly assessing writing quality is what type of scoring procedure will be used: Should a single score be given to each text, or should the different features of a text be scored separately? This issue has been the subject of a great deal of research and discussion in the composition literature. Among others, two types of scoring procedures have mainly been discussed: analytic and holistic scoring.